Improving the sustainability index through life cycle assessment: A case study in a bag manufacturing company - Nabila, Shadrina Putri; Sari , Emelia; Marie , Iveline Anne; Sari , Indah Permata; Abu , Mohd Yazid (OPSI, 2025)
The bag manufacturing industry is one of the most resource-intensive and environmentally impactful sectors, producing significant waste and emissions during manufacturing. This study focuses on the Audero Bag, a product of the Less Catino brand, which contributes the most to production waste among all models. This research applies the Life Cycle Assessment (LCA) method following ISO 14040:2006 to evaluate the environmental impact of each production stage, from material cutting to finished goods, within a gate-to-gate system boundary using SimaPro software. The results show that the Cutting Division contributes the highest environmental impact (88.4%) due to substantial material waste and energy consumption. The most dominant impact categories identified are terrestrial ecotoxicity (6.27E-03), marine aquatic ecotoxicity (4.90E-03), and freshwater aquatic ecotoxicity (1.72E-03) caused by fabric material usage. The sustainability assessment based on economic, environmental, and social indicators yields an overall Sustainability Index (SI) of 80.68%, indicating a relatively good level of performance. After the implementation of proposed 6R improvement strategies (Reduce, Reuse, Recycle, Repair, Remanufacture, and Recover) the index improved to 66.51%, reflecting the need for a more balanced integration of efficiency and environmental management. Strengthening waste treatment systems and optimizing material recovery are recommended to enhance long-term sustainability performance in the bag production process.